2021
DOI: 10.1021/acsami.1c08798
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun One-Dimensional Electrocatalysts for Oxygen Reduction Reaction: Insights into Structure–Activity Relationship

Abstract: Oxygen reduction reaction (ORR) is an efficiency-determining process at the cathode in several energy storage and conversion devices, typically such as metal-air batteries and fuel cells. To date, a considerable amount of ORR electrocatalysts have been purposely exploited to address the key issues of high overpotentials and sluggish electrochemical kinetics. Electrospinning is a popular additive manufacturing technology, enabling the production of one-dimensional (1D) electrocatalysts with outstanding chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 143 publications
(344 reference statements)
0
23
0
Order By: Relevance
“…1). 45 A syringe pump is usually involved to ensure a stable and controllable infusion rate of the polymer solution. And the forming process of electrospun materials usually involves the following consecutive procedures.…”
Section: Fundamentals Of Electrospinningmentioning
confidence: 99%
See 2 more Smart Citations
“…1). 45 A syringe pump is usually involved to ensure a stable and controllable infusion rate of the polymer solution. And the forming process of electrospun materials usually involves the following consecutive procedures.…”
Section: Fundamentals Of Electrospinningmentioning
confidence: 99%
“…[42][43][44] Among them, the 1D nanofibers and nanotubes gradually appealed to the interest of scientists, due to the advantages of large specific surface area, high aspect ratio, and efficient electron transfer. 45 Nowadays, numerous synthetic strategies have been proposed to generate fiber-shaped materials such as hydrothermal synthesis, chemical vapor deposition, and electrospinning, among which electrospinning provides a simple and versatile platform for the creation of 1D nanomaterials with tunable composition and nanostructures. In addition, it is also reported that electrospinning methods are ecofriendly and economical for the production of 1D fiber-shaped or tube-like nanomaterials with controllable architectures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these techniques, the electrospinning is a simple and versatile approach for producing 1D nanofibers from a wide variety of materials, with representative examples including metals, polymers, ceramics, and organic–inorganic composites [ 16 18 ]. Unlike other ways for generating 1D nanomaterials, the nanofibers obtained by electrospinning have obvious advantages in composition control, structure design, and function expansion [ 19 21 ]. Moreover, the electrospun nanofibers combine distinctive features such as fine diameter, large specific surface area, and high porosity, thus meeting the needs of diverse applications [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…for environmental applications, 60 modified TiO 2 confined catalysts for photo-catalysis, 61 and 1D materials prepared using the electro-spinning method for the oxygen reduction reaction (ORR). 62 However, 1D catalysts confined within SiO 2 , TiO 2 , CeO 2 NTs etc. via the coating method for thermal catalysis have not been systematically reviewed.…”
Section: Introductionmentioning
confidence: 99%